2022
DOI: 10.3390/ijerph19106188
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interventions Led by Community Pharmacists in Primary Care for Adults with Type 2 Diabetes Mellitus on Therapeutic Adherence and HbA1c Levels: A Systematic Review

Abstract: Type 2 diabetes mellitus has been assessed as a widespread disease globally. Unfortunately, this illness can occasionally go undetected and without symptoms until it reaches the emergency condition, and this can be notably true in patients who do not receive routine medical care. Pharmacists are the foremost accessible health care providers. They can help patients select the most appropriate hypoglycemic management strategy through their experiences. This review aimed to provide an overview of the literature p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…First, because all the patients with and without sarcopenia were enrolled from an Asian population, the corresponding ethnic susceptibility compared with that of a non-Asian population remains unclear; hence, our results should be cautiously extrapolated to non-Asian populations, however, no study has demonstrated significant differences in sarcopenia between Asian and non-Asian patients with diabetes. Second, although the aDCSI (severity of diabetes) has been matched, the therapy of carbohydrate metabolism disorders and whether patients were adherent to this therapy during the observation period were unavailable [ 53 , 54 ]. Third, the diagnoses of all comorbid conditions were based on ICD-9-CM or ICD-10-CM codes.…”
Section: Discussionmentioning
confidence: 99%
“…First, because all the patients with and without sarcopenia were enrolled from an Asian population, the corresponding ethnic susceptibility compared with that of a non-Asian population remains unclear; hence, our results should be cautiously extrapolated to non-Asian populations, however, no study has demonstrated significant differences in sarcopenia between Asian and non-Asian patients with diabetes. Second, although the aDCSI (severity of diabetes) has been matched, the therapy of carbohydrate metabolism disorders and whether patients were adherent to this therapy during the observation period were unavailable [ 53 , 54 ]. Third, the diagnoses of all comorbid conditions were based on ICD-9-CM or ICD-10-CM codes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, community pharmacists who conducted medication reviews and provided educational counseling were the most common in the 9 included literature searches [16-24]. These are followed by specialized care services for speci c diseases or illnesses being offered by community pharmacists, as underlined in 9 included studies; these services include the management of anticoagulation, minor ailments, epilepsy care, chronic pain intervention, obesity, weight services, medicine and alcohol consultation, and other chronic disease care such as diabetes and hypertension [16,20,[25][26][27][28][29][30][31] Among the included studies, 3 highlighted the expansion of community pharmacists' services and their responsibilities in preserving the continuity of care for society during public health emergencies [32][33][34]. Community pharmacists also contributed to chronic disease management during the COVID-19 pandemic, maintaining the drug supply to the public, serving as vaccinators and screeners, and performing COVID-19 diagnostic tests.…”
Section: Study Selectionmentioning
confidence: 99%
“…Additionally, they can aid in the management and prevention of chronic conditions like metabolic syndromes, diabetes, and cardiovascular diseases, which will improve patient care (George et al, 2010 ; Erku et al, 2017 ; Belachew et al, 2020 ; Yousuf et al, 2019 ; Dhippayom et al, 2013 ; Katangwe et al, 2019 ; Malik et al, 2022 ). It was also discovered that a diabetic intervention provided by CPPs had better results in treatment outcome (Ali et al, 2012 ; Malik et al, 2022 ; Farag Mohamed et al, 2021 ; Al Assaf et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%